Gambaran Tekanan Darah Sebelum dan Sesudah Senam Hipertensi pada Lansia Hipertensi di Desa Kaling Tasikmadu - Siti Sundari; Sri Hartutik (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Hypertension is blood pressure above the normal value, namely systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Elderly people are easily at risk of developing hypertension. The prevalence of hypertension according to WHO in 2021 is 1.28 billion in the world, while according to the Ministry of Health in 2019, the highest hypertension disease is in the province of Kalimantan as much as 44.1%. In this study, to determine the description of blood pressure before and after hypertension exercise in the elderly with hypertension in the village of Kaling, Tasikmadu, Karanganyar. Descriptive research design using Simple Random Sampling method with inclusion and exclusion criteria, a total sample of 16 people, the measurement tool using a sphygmomanometer. Analysis of this data using the univariate method in the form of a descriptive percentage. Univariate test showed that the majority of hypertension are elderly and female. Before hypertension exercise, the majority of respondents experienced hypertension in the category of hypertension grade 1, after being given hypertension exercise, the majority of blood pressure became normal. There was a decrease in blood pressure in the elderly with hypertension in the village of Kaling Tasikmadu Karanganyar after hypertension exercise was carried out from hypertension grade 1 to the normal category.